2021
DOI: 10.1038/s41564-021-01000-z
|View full text |Cite
|
Sign up to set email alerts
|

Global phylogeny of Treponema pallidum lineages reveals recent expansion and spread of contemporary syphilis

Abstract: Syphilis, which is caused by the sexually transmitted bacterium Treponema pallidum subsp. pallidum, has an estimated 6.3 million cases worldwide per annum. In the past ten years, the incidence of syphilis has increased by more than 150% in some high-income countries, but the evolution and epidemiology of the epidemic are poorly understood. To characterize the global population structure of T. pallidum, we assembled a geographically and temporally diverse collection of 726 genomes from 626 clinical and 100 labo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
76
1
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 62 publications
14
76
1
10
Order By: Relevance
“…Syphilis is a globally prevalent multisystemic and chronic infection caused by the spirochetal bacterium Treponema pallidum subspecies pallidum ( T. pallidum ). 1 It can be transmitted through blood transfusion and derivatives, unprotected sexual intercourse and maternal-neonatal transmission. Syphilis is still a major public health problem, with estimated 36 million occurrences and 12 million new cases worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Syphilis is a globally prevalent multisystemic and chronic infection caused by the spirochetal bacterium Treponema pallidum subspecies pallidum ( T. pallidum ). 1 It can be transmitted through blood transfusion and derivatives, unprotected sexual intercourse and maternal-neonatal transmission. Syphilis is still a major public health problem, with estimated 36 million occurrences and 12 million new cases worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Genome sequencing revealed that two major TPA lineages, Nichols and SS14, co-circulate across multiple continents. The genetically homogeneous SS14 lineage was the dominant lineage in most sampled regions; however, both lineages exhibited similar phylodynamics and are responsible for current epidemics 1 3 . Furthermore, TPA populations circulating among patients in the twentieth century may have been different from the modern populations 1 , 3 .…”
mentioning
confidence: 99%
“…The genetically homogeneous SS14 lineage was the dominant lineage in most sampled regions; however, both lineages exhibited similar phylodynamics and are responsible for current epidemics 1 3 . Furthermore, TPA populations circulating among patients in the twentieth century may have been different from the modern populations 1 , 3 . This has been linked to a population bottleneck in the late 1990s, followed by the expansion of modern sublineages in the 2000s.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chama atenção a repetição de casos em uma mesma família. Para caracterizar a estrutura populacional global de T. pallidum,Beale et al, 2021 sequenciaram amostras de 23 países em todo o mundo e analisaram as sequências do genoma e concluíram que todos os 726 genomas pertenciam a apenas duas linhagens, Nichols e SS14, com o último dominando e ambos circulando globalmente(Aoroa, 2016;Beale, 2019; Beale et al,2021).…”
unclassified